The National Recovery Administration and the Rubber Tire Industry, 1933–1935 - Pennock, Pamela (Business History Review, 1997)
In the 1920s and 1930s, the rubber tire industry faced debilitating challenges, mostly brought about by changes in the industry's retail structure and exacerbated by the Great Depression. Segments of the industry attempted to use the New Deal's NRA codes to solve these new problems and stabilize the tire market, but the tire manufacturing and tire retailing codes were patent failures. Instead of leading to cartelization and higher prices, which is what most scholars assume the NRA codes did, the tire industry codes actually led to even more fragmentation and price-cutting.
Keywords: Business History and gender